Temporal Approach, Digitally Assisted Phacovitrectomy in a Patient with Severe Kyphosis due to Axial Spondyloarthritis - J. Rios-Nequis Geovanni; J. Abel Ramírez-Estudillo; L. Daniel Gutiérrez-García; Martin Jiménez-Rodríguez; Arthur Levine-Berevichez (Case Reports in Ophthalmological Medicine)
Purpose. To describe a temporal approach, digitally assisted phacovitrectomy in a patient with severe kyphosis due to axial spondyloarthritis. Case Report. A 70-year-old male patient with proliferative diabetic retinopathy with vitreous hemorrhage and cataract and ankylosing spondylitis with severe kyphosis. A temporal approach, digitally assisted 25 G phacovitrectomy was performed with a Constellation platform and the NGENUITY visualization system. The Trendelenburg position was utilized. Conclusion. A temporal approach, digitally assisted phacovitrectomy may be used in select cases of severe kyphosis with positive outcomes.